Assessing the eligibility of Brainomix e-ASPECTS for acute stroke imaging - Dorochowicz, Mateusz; Kacała, Arkadiusz; Puła, Michał; Korbecki, Adrian; Kosikowska, Aleksandra; Tołkacz, Aleksandra; Zimny, Anna; Guziński, Maciej (Frontiers in Neuroinformatics, 2025)
BackgroundTimely and accurate assessment of acute ischemic stroke is crucial for determining eligibility for mechanical thrombectomy. The Alberta Stroke Program Early CT Score (ASPECTS) is a widely used tool for evaluating early ischemic changes on non-contrast CT (NCCT), but its interpretation is subject to interobserver variability. Brainomix e-ASPECTS is an automated software designed to standardize and expedite this assessment. We aimed to evaluate the clinical utility and diagnostic performance of the Brainomix e-ASPECTS software in an unselected, real-world cohort of patients undergoing NCCT for suspected acute ischemic stroke.MethodsWe retrospectively analyzed 1,029 NCCT studies from 954 patients between March 2020 and December 2024. e-ASPECTS scores were compared to radiologist-assigned ASPECTS, which served as the reference standard. Diagnostic accuracy, sensitivity, specificity, and correlation between scoring methods were assessed.ResultsThere was a strong correlation between e-ASPECTS and radiologist ASPECTS (ρ = 0.953, p < 0.001). For detecting acute ischemia, sensitivity was 95.8% (95% CI, 93.6–97.3%), specificity 96.9% (95% CI, 94.7–98.2%), and overall accuracy 96.3% (95% CI, 95.1–97.5%). The positive predictive value was 97.2% (95% CI, 95.3–98.4%), and the negative predictive value was 95.3% (95% CI, 92.8–96.9%). Score concordance was high, with exact matches in 92.3% of cases and a ≤ 1-point difference in 97.7%. Misclassification for thrombectomy eligibility (ASPECTS < 6) occurred in four cases (0.4%). The software achieved a processing success rate of 91.9%.ConclusionE-ASPECTS demonstrates high diagnostic accuracy and strong agreement with expert radiological assessment, supporting its role as a valuable decision support tool in acute stroke imaging. However, its use should complement, not replace, expert interpretation, particularly in patients with low ASPECTS scores, where treatment decisions are most sensitive.